Genotoxicity in the oral cells of older people from a Brazilian rural area: a population-based study - Luana Soares KUZE; João Paulo DE CARLI; Júlia Stephanie PRESOTTO; Kaue COLLARES; Alvaro DELLA BONA (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The purpose of this population-based, observational, and cross-sectional study was to evaluate alterations in the oral cells of a population of older people from a Brazilian rural area, using the micronucleus technique to investigate possible associated genotoxic factors. A questionnaire was applied and clinical examination and collection of oral mucosal cells were performed for all older people (≥ 60 years) from a town in southern Brazil. Demographic and socioeconomic variables, deleterious habits (drinking and tobacco use), presence of gastro-oesophageal reflux disease (GERD), and the use of proton pump inhibitors (PPIs) were considered the exposure variables, whereas metanuclear changes (MCs) and the prevalence of cell micronuclei (MN) were considered outcomes. Out of 489 older people, 447 were included in the study, among whom 50.8% were men with a mean age of 70.9 years and 83.9% had a monthly family income greater than US$ 500.00. GERD symptoms were present in 36.2% of the individuals, and 29.1% used PPIs daily, 53.3% consumed alcoholic beverages, and 46.7% used tobacco. The analysis of 1,000 oral mucosal cells per subject showed a MN frequency of 0-2 per individual, and MCs were detected with an average of 15 units per individual (median = 11 per individual). Poisson regression did not show statistical association between the exposure variables and the outcomes (presence of MN and MCs), except for the use of PPIs, which was a protective factor for the prevalence of MN [PR 0.6 (CI 0.3-0,9)]. Age, sex, family income, tobacco use and drinking, and GERD were not associated with the number of MN and MCs in oral mucosal cells of the investigated older people.